Efficiency of Private Sector Banks in India - Narayanaswamy, T.; Muthulakshmi, A. P. (Indian Journal of Finance, 2014)
This paper examined the relative efficiency of all the private sector banks in India from 2008 to 2013 using the data envelopment analysis (DEA) methodology. Axis Bank, Kotak Mahindra Bank, and ICICI Bank were relatively efficient in terms of technical efficiency, pure technical efficiency, and scale efficiency. The average (overall) technical inefficiency score during the study period was found to be 6%. In terms of pure technical efficiency, apart from the above three banks, HDFC Bank and Nainital Bank were also relatively efficient. The average (overall) pure technical inefficiency score during the study period was found to be 5%. Positive correlation ranging from 0.7 to 0.95 was observed between return on assets and different types of efficiencies during the study period (except for the year 2008-09). Negative correlation ranging from -0.3 to 0.5 was observed between non - performing assets ratio and different types of efficiencies during the study period (except for the year 2008-09).